2002
DOI: 10.1002/cncr.10319
|View full text |Cite
|
Sign up to set email alerts
|

Survival differences among Asian subpopulations in the United States after prostate, colorectal, breast, and cervical carcinomas

Abstract: BACKGROUNDInformation is limited for Asian subgroups regarding survival after diagnosis of the common cancers amenable to routine screening. The authors examined survival after carcinomas of the prostate, colon/rectum, breast, and cervix separately for Chinese, Japanese, Filipinos, and non‐Hispanic whites in the United States.METHODSUsing data from the Surveillance, Epidemiology, and End Results program, the authors compared the distributions of stage at diagnosis and computed 5‐year cause specific survival pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
65
0

Year Published

2003
2003
2011
2011

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 112 publications
(66 citation statements)
references
References 34 publications
1
65
0
Order By: Relevance
“…These results are consistent with those of earlier studies mostly focusing on single forms of cancers (Flood et al, 2000;Pineda et al, 2001;Lin et al, 2002;McGuire et al, 2002;Hashibe et al, 2003;Pagano et al, 2003;Chien et al, 2005;Gomez et al, 2007;Sun et al, 2007). Existing differences probably lie more in biological factors than health care-related factors.…”
Section: Discussionsupporting
confidence: 92%
“…These results are consistent with those of earlier studies mostly focusing on single forms of cancers (Flood et al, 2000;Pineda et al, 2001;Lin et al, 2002;McGuire et al, 2002;Hashibe et al, 2003;Pagano et al, 2003;Chien et al, 2005;Gomez et al, 2007;Sun et al, 2007). Existing differences probably lie more in biological factors than health care-related factors.…”
Section: Discussionsupporting
confidence: 92%
“…29 A SEER-wide study of breast carcinoma diagnosed in females in the 1988 -1994 period found higher stage-adjusted survival rates for Japanese females than for Chinese, Filipinas, or whites. 18 A previous study of breast carcinoma survival in the San Francisco Bay Area showed that for women diagnosed with local disease, Filipinas had significantly lower relative survival than whites. 17 By combining all APIs into one category, we may have obscured the higher survival of the Japanese with the lower survival of the Filipinas.…”
Section: Survival In Apismentioning
confidence: 97%
“…9,[12][13][14][15] International studies of breast carcinoma have shown better survival for Japanese than Caucasians, 16 but most studies report similar survival rates for Asians and whites within the United States. 12,[17][18][19] In addition, although race/ethnicity, disease stage, and SES are correlated, SES measures have not been included in most studies of Asian and Hispanic women. Previous studies of survival by race/ ethnicity were limited by the lack of data on SES and tumor characteristics, inclusion of in situ disease with local stage disease, and inadequate statistical power due to small sample sizes.…”
mentioning
confidence: 99%
“…45,46 Future analyses should disaggregate the R/E categories so that we can better understand these findings. 11,44 The use of aggregate-based measures to assign individual SES status is suboptimal. 20 However, aggregate measures of income at the community level remains valuable because community-level predictors of SES have been shown to be a strong predictor of healthcare services and health outcomes for all individuals living in that community (both high and low income).…”
Section: Strengths/limitationsmentioning
confidence: 99%
“…Possible explanations include differences in screening mammography leading to differences in the stage and size of tumors at diagnosis, 5,6 tumor biology, inadequate receipt of appropriate breast cancer treatment, 5 and underlying patient comorbidities and socioeconomic factors. [7][8][9][10][11] Several studies have used Surveillance, Epidemiology, and End Results (SEER) program information to explore these issues. 3,4,[12][13][14][15][16][17][18] Although SEER data include valuable regional information on a large, geographically diverse population, it lacks detailed information concerning screening mammography use and underlying comorbidities that may impact survival.…”
mentioning
confidence: 99%